IMPLEMENTING A HYBRID MODEL OF TGFU AND FITNESS EDUCATION TO IMPROVE PHYSICAL FITNESS AND SOCIAL INTELLIGENCE OF ELEMENTARY STUDENTS - Sartika, Jenifer Aprilia; Putri, Wulandari; Nugroho, Wildan Alfia; Mahendra, Agus; Lubay, Lukmannul Haqim (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2025)
This study aims to improve students’ physical fitness and social intelligence through the implementation of a hybrid model combining Teaching Games for Understanding (TGFU) and Fitness Education. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The subjects were 28 fifth-grade students at SDPN 252 Setiabudi. Each cycle consisted of three stages: two learning interventions and one evaluation. Instruments used in the study included the Indonesian Students' Physical Fitness Test (TKSI) and the Social Intelligence Scale (TSIS). The results showed that the hybrid TGFU and Fitness Education model progressively improved students’ physical fitness levels from lower to higher categories. In the pre-cycle stage, low categories such as